The Evolving Landscape of Psoriasis Treatment: Current Biologics and Novel Targets - Pacek, Szymon; Muda, Martyna; Paweł Kalinowski; Bachurski, Patryk; Wiśniewski, Karol Paweł; Maja Międlar; Elisabetta Pierzga; Zarański, Bartosz; Chmiel, Gabriela; Witkowski, Paweł (Journal of Education, Health and Sport, 2026)
Introduction. Psoriasis is recognized as an auto- immune inflammatory disorder characterized by hyperproliferation of keratinocytes and infiltration of T- cells. Disease can occur at any age and may cause episodes of depression and psoriatic arthritis. Currently the researchers are trying to find the most valuable and specific targets in treatment. Purpose. The primary purpose of our review is to provide comperhensive update on the most valuable and possibly best new rapidly evolving scientific approaches in treatment of chronic disease such as psoriasis. Materials and Methods. We have reviewed PubMed data base in order to identify clinical trials, meta analyses and randomized controlled trials form the past 5 years. Results. The review confirms the IL-23/IL-17 axis as the primary pathogenic driver. While management utilizes effective topical, systemic, phototherapy, and advanced biological agents (TNF-alpha, IL-17, and IL-23/IL-12 inhibitors), the continued therapeutic challenge, particularly for refractory patients, drives the need for innovative treatments. The emergence of the first oral, selective allosteric TYK2 inhibitor (deucravacitinib) and ongoing research into targets like IL-21 and the microbiota highlight the rapidly evolving landscape of psoriasis therapy.